Asset Specificity of Nonfinancial Firms - Kermani, Amir; Ma, Yueran (Quarterly Journal of Economics, 2022)
Abstract We develop a new data set to study asset specificity among nonfinancial firms. Our data cover the liquidation values of each category of assets on firms’ balance sheets and provides information across major industries. First, we find that nonfinancial firms have high asset specificity. For example, the liquidation value of fixed assets is 35% of the net book value in the average industry. Second, we analyze the determinants of asset specificity and document that assets’ physical attributes (e.g., mobility, durability, and customization) play a crucial role. Third, we investigate several implications. Consistent with theories of investment irreversibility, high asset specificity is associated with less disinvestment and stronger effects of uncertainty on investment activities. We also find that the increasing prevalence of intangible assets has not significantly reduced firms’ liquidation values.